TUTORIAL GUIDANCE THROUGH BLENDED LEARNING IN IMPROVING AN ABILITY NURSING EDUCATION COMPETENCY - Uliyah, Musrifatul; Nurlaela, Luthfiyah; Mustaji; alimul hidayat, Abdul aziz; Dede Nasrullah (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: to analyze the effect of tutoring through the blended learning in improving the ability in pre test of nurses competency results. Method: This research used pre-experimental study design, the number of respondents was 60 respondents. Samples were taken by simple random sampling. The inclusion criteria of the study sample were: final semester students who would face competency exams who were not in a sick condition. The data was collected using the nurse competency test. With a total of 120 questions with the results of the Cronbach’s alpha test on the competency test variable is 0.95. The data analysis used descriptive statistics to calculate the characteristics of respondents with frequency distribution, percentage, mean and standard deviation (sd). Paired t test is used to analyze the effect of differences that were before and after tutoring through the blended learning. Results: showed the implementation of tutoring through the blended learning that are showing differences before and after following the tutorial guidance program through blended learning, with the test value paired t test p = 0.000. Other results from tutoring through the blended learning are in-house training and online training services, 9 (nine) enrichment book products for nurse competency tests. Conclusion: to improve the results of the nurse competency test that the guidance can be made in tutorials and online through program blended learning. Thus tutoring through blended learning can be used as an alternative guidance for nursing competency tests for nursing students who can prepare nurse competency tests in Indonesia.